The Effect of Contextual Teaching and Learning (CTL) with QuizWhizzer on Learning Outcomes in Islamic Religious Education - Utami, Ladia Dwi; Iryanti, Shobah Shofariyani (Belajea: Jurnal Pendidikan Islam, 2025)
This study examines the effectiveness of the Contextual Teaching and Learning (CTL) model integrated with the Quizwhizzer application compared to conventional methods. The research employs a quasi-experimental design with a pretest-posttest control group design at SMA Islam Harapan Ibu, South Jakarta. The study sample consists of 38 students, divided into an experimental group (19 students) using the CTL model with Quizwhizzer assistance and a control group (19 students) using conventional methods. Data collection was conducted through learning achievement tests. Data analysis utilized the Paired Sample T-Test to measure differences in learning outcomes within each group before and after treatment, and the Independent Sample T-Test compared learning outcomes between the experimental and control groups after treatment. The results indicate that the CTL model integrated with Quizwhizzer significantly improves student learning outcomes. The average pretest score for the experimental group increased from 65.42 to 85.79, while the control group improved from 64.37 to 74.21. The Paired Sample T-Test showed a significance value of 0.000 < 0.05, indicating a significant improvement within each group. The Independent Sample T-Test also showed a significance value of 0.012 < 0.05, meaning there was a substantial difference between the experimental and control groups after treatment. These findings emphasize integrating the CTL learning model and technology in Islamic Religious Education (PAI) to create an interactive and relevant learning experience.